A Generalization of a Greguš Fixed Point Theorem in Metric Spaces - Marwan A. Kutbi; A. Amini-Harandi; N. Hussain (Journal of Applied Mathematics)
We first introduce a new class of contractive mappings in the setting of metric spaces and then we present certain Greguš type fixed point theorems for such mappings. As an application, we derive certain Greguš type common fixed theorems. Our results extend Greguš fixed point theorem in metric spaces and generalize and unify some related results in the literature. An example is also given to support our main result.